Climate change and habitat heterogeneity drive a population increase in Common Buzzards Buteo buteo through effects on survival. (27th November 2013) - Jonker, Rudy M.; Chakarov, Nayden; Krüger, Oliver; Sergio, Fabrizio
<x xml:space="preserve">Abstract</x> The effect of changing climatic conditions on wild populations has been the subject of much recent research. Most attention has been on the direct effects of climate changes on species of lower trophic levels and on the negative consequences of climate change. However, a deeper understanding of how climate change affects apex predators is vital, as they are keystone species that have a disproportionate effect on ecosystems. Studying survival in an apex predator requires individual‐based data from long‐term studies and is complicated by the integration of climatic effects on lower trophic levels. Here we assess how climate affects the survival of the Common Buzzard Buteo buteo. We analysed the survival of 670 males and 669 females over the period 1989–2011, during which time our study population quadrupled. We used mark–recapture survival analysis of individual resightings of breeding adults to identify the environmental factors best explaining survival. A decrease in the North Atlantic Oscillation (NAO) index increased survival to an extent that largely explains the population increase. This might be caused by higher Common Vole Microtus arvalis survival in drier conditions and under snow cover. Buzzard survival appeared to increase more for males than for females, possibly due to the males' higher sensitivity to winter food availability resulting from their smaller body mass. However, we also found that the effect of NAO strongly depended on the area in which individuals lived, especially for females. This may have been caused by the recolonization of Eagle Owls Bubo bubo in some parts of our study area. This study suggests that climatic changes can have complex effects on species of higher trophic levels via an interaction with their prey.